Environmental Noise from Construction Site Power Systems and its Mitigation. (March 2014) - Sellappan, Elancheliyan; Janakiraman, Krishnakumar
Generator sets for power are among the equipment used in the construction industries, used in large numbers and as clusters and also located very near to the work area. The noise levels produced by these generators are much higher than the permissible limit. The first part of this paper assesses the potential noise emissions associated with two unclosed caterpillar power generators used in a construction site. In the second part combined noise effects of generators and other activities are studied over a 12-hour period to establish background environmental noise levels. The study shows large number of construction workers working nearby generators are exposed to 100 dB (A) or more noise. The chain of noise control at the source – along the noise path or at the receiver – and what effective steps could be taken to mitigate the noise exposure at each stage are considered.